pls help me out in this question .......
pls give the whole process.......
Attachments:
![](https://hi-static.z-dn.net/files/d06/a0806a040324d68c5f7dd749f00ed3d2.jpg)
Answers
Answered by
1
Answer:
Hope you understand ❤️ please make brainlist
Attachments:
![](https://hi-static.z-dn.net/files/db1/474b10a9c6b6b107b64b6de5eb04c9f2.jpg)
Answered by
1
Answer:
given
a+b+c=0
then
a+b=-c
b+c= -a
a+c=-b
now substitute in question
given a+b+c=0
then
the value of given question
is =0/abc
=0
hope this helps you
Similar questions